2023
DOI: 10.1093/nsr/nwad143
|View full text |Cite
|
Sign up to set email alerts
|

Programmable deaminase-free base editors for G-to-Y conversion by engineered glycosylase

Abstract: Current DNA base editors contain nuclease and DNA deaminase that enables deamination of cytosine (C) or adenine (A), but no method for guanine (G) or thymine (T) editing is available now. Here we developed a deaminase-free glycosylase-based guanine base editor (gGBE) with G editing ability, by fusing Cas9 nickase with engineered N-methylpurine DNA glycosylase protein (MPG). By several rounds of MPG mutagenesis via unbiased and rational screening using an intron-split EGFP reporter, we demonstrated that gGBE wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 48 publications
4
21
0
Order By: Relevance
“…3a and Supplementary Fig. 6i), consistent with previous findings of gGBE 3 , AYBE 9 and CGBEs 1115 . We found that gTBEv3 also induced indels with frequency ranging from 5.2% to 45.2% at the 20 edited sites (Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…3a and Supplementary Fig. 6i), consistent with previous findings of gGBE 3 , AYBE 9 and CGBEs 1115 . We found that gTBEv3 also induced indels with frequency ranging from 5.2% to 45.2% at the 20 edited sites (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Encouraged by the development of gGBE in our previous study 3 , we attempted to develop thymine and cytosine base editor using the deaminase-free glycosylase-based strategy. Since the three pyrimidine bases (i.e., T, C, and U) are structurally similar, we speculated that excision of canonical T or C could be achieved by engineering certain uracil DNA glycosylase, thus triggering the BER pathway and facilitating direct T editing or C editing following the one-step generation of AP sites (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we showed that the rifampin assay, which was used to identify suitable split sites, was feasible for cytosine deaminases as well as for adenine deaminases. Thus, this strategy can be applied to other deaminases, such as APOBEC3B, [ 59 ] TadA orthologs, [ 70 ] and even the non‐deaminase N‐methylpurine DNA glycosylase, [ 71 ] which has been shown to achieve G‐to‐Y editing.…”
Section: Discussionmentioning
confidence: 99%